Assessing the influence of autumnal temperature fluctuations on cold hardiness in different grapevine cultivars: variations across vine age and bud positions - Kaya, Ozkan; Delavar, Hava; Shikanai, Avery; Auwarter, Collin; Hatterman-Valenti, Harlene (Frontiers in Plant Science, 2024)
The dynamic fluctuations in autumn temperatures, particularly the marked diurnal variations and the subsequent precipitous drops are key and a pivotal role in viticulture, as they critically influence the acclimation process of grapevines to cold, thereby directly impacting their survival and productivity in cold-climate regions. In this comprehensive study, we investigated the cold hardiness of four grapevine cultivars: 'Itasca', 'Frontenac', 'La Crescent', and 'Marquette', focusing on how these cultivars and their individual buds (1 st , 2 nd , 3 rd , 4 th , 5 th , 6 th , 7 th , 8 th , and 9 th ) respond to fluctuating weather and low temperatures typical of autumn (-1.1°C (30°F) -9.4°C (15°F ) and -17.8°C (0°F)). Our results illuminated the striking variability in cold hardiness that was manifest not only among the different cultivars but also within individual buds on the same vine, underscoring the critical influence of bud position on a vine for cold hardiness. 'Frontenac' showed greater cold hardiness at critical temperatures at which 10%, and 50% of the dormant buds were lethally affected by cold (LT10 and LT50) compared to 'Itasca' and 'La Crescent', with 'Marquette' exhibiting intermediate values. However, in cultivars such as 'Itasca' and 'Marquette', certain buds demonstrated a pronounced hardiness when faced with colder temperatures, while others exhibited a heightened sensitivity, thereby revealing a nuanced interplay between bud position and a vine's ability to withstand cold stress. Our study revealed a notable divergence from traditional viticulture understanding; apical buds demonstrated greater cold hardiness than basal buds and opened new paths for research into grapevine physiology. Our results also indicated a significant trend wherein older vines across all studied cultivars displayed enhanced cold hardiness, particularly pronounced at the critical LT50 and the critical temperature at which 90% of the dormant buds were lethally affected by cold (LT90) thresholds, in comparison to younger vines.